Divide and Profit - Beall, Jo (PINS-Psychology in Society, 2025)
DIVIDE AND PROFIT: INDIAN WORKERS IN NATAL by Shamim Marie (Worker Resistance and Culture Publications, Durban: 1986. Cost is R4,50 and R2,00 to trade union members). This book is the first from Worker Resistance and Culture Publications. It is aimed not at an academic readership but rather at workers and is accompanied by a slide-tape package if desired. As stated in the introduction, 'It is hoped that the book will be used in a number of ways. Some may want to read it for interest and maybe enjoyment. It could be used as a resource for organisation, or it could be used as part of shop steward and worker discussion or education' (Marie:1986, 5). This is not to say that it should not be read by academics as well, however, and not only for enjoyment. For the book provides an excellent example of how to make a vast collection of material and difficult concepts accessible to a wider audience, a useful and necessary skill for intellectuals to develop.